“I haven’t had that much fun since labour.” Subtitling sarco-ironic remarks in Gilmore Girls - Lampiniva, Satu (My University, 2016)
The purpose of this study is to explore how the potential cues of spoken sarcasm and irony are transferred into written Finnish subtitles in the American television series Gilmore Girls. The aim is to discover how the use of cuing differs between the English source text and the Finnish target text. The research is conducted through qualitative and quantitative analysis and comparison between the two languages. Three (3) episodes from Gilmore Girls are analysed using the Finnish DVD subtitles and the episodes’ English unofficial transcripts. The sarco-ironic remarks and their translations are identified, and their individual sarco-ironic cues are categorised. The number of cues, the number of cues in each category and the number of cue shifts are compared quantitatively in order to find whether the translator uses less or different cues than the writer of the original source text. The qualitative analysis focuses on the cue types used in both texts. The results confirmed the hypothesis of sarcasm and irony being relatively straightforward linguistic phenomena to translate, and the hypothesis of the category of words of reinforcement/trivialising being the most used in conveying sarcasm and irony. However, the study also showed that even though some cues were cut in the translation process, the sarco-ironic meaning was rarely omitted entirely from the translation. The findings also showed that the number of cue shifts was surprisingly low. From these results we can deduce that at least in the context of DVD subtitles, sarcasm and irony can be conveyed also in writing, and even though some cues were omitted or shifted, sarcasm and irony were still detectable in the Finnish subtitles. The language used in DVD translations uses less cues of sarcasm and irony and it could thus be considered less versatile than the original source language.